1989
DOI: 10.1002/cne.902880108
|View full text |Cite
|
Sign up to set email alerts
|

Immunoelectron‐microscopic localization of the 180 kD component of the neural cell adhesion molecule N‐CAM in postsynaptic membranes

Abstract: In order to investigate the expression of cell adhesion molecules in synapses, we have studied the localization of the neural cell adhesion molecule N-CAM in the cerebellum and hippocampus of adult mice by immunocytological and immunochemical methods. Of the three molecular components of N-CAM with relative molecular masses (Mr) of 120, 140, and 180 kD, N-CAM 120 is not detectable in synaptosomal membranes, whereas N-CAM 140 is expressed on both pre- and postsynaptic membranes and N-CAM 180 is restricted to po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
98
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(111 citation statements)
references
References 46 publications
13
98
0
Order By: Relevance
“…This deficit not only confirms the observed inability of VPA-treated animals to acquire and consolidate the water maze paradigm (Murphy et al, 1996;Sandi et al, 2004) but may also be relevant to the social approach avoidance abnormalities that are observed in these animals. NCAM-null mice, for example, exhibit social deficits manifested by increased aggression, an effect that is counteracted by the introduction of transgenic NCAM180 (Stork et al, 2000), the synapse-specific isoform that carries PSA in adult animals (Persohn et al, 1989;Doyle et al, 1992). Moreover, mice lacking the polysialyltransferase that regulates NCAM PSA in adulthood (PST or ST8SiaIV) also exhibit social deficits and these become even more severe in mice lacking the developmental enzyme (STX or ST8SiaII) (Calandreau et al, 2010).…”
Section: Construct Validity Of Vpa Model Of Asdmentioning
confidence: 99%
“…This deficit not only confirms the observed inability of VPA-treated animals to acquire and consolidate the water maze paradigm (Murphy et al, 1996;Sandi et al, 2004) but may also be relevant to the social approach avoidance abnormalities that are observed in these animals. NCAM-null mice, for example, exhibit social deficits manifested by increased aggression, an effect that is counteracted by the introduction of transgenic NCAM180 (Stork et al, 2000), the synapse-specific isoform that carries PSA in adult animals (Persohn et al, 1989;Doyle et al, 1992). Moreover, mice lacking the polysialyltransferase that regulates NCAM PSA in adulthood (PST or ST8SiaIV) also exhibit social deficits and these become even more severe in mice lacking the developmental enzyme (STX or ST8SiaII) (Calandreau et al, 2010).…”
Section: Construct Validity Of Vpa Model Of Asdmentioning
confidence: 99%
“…These data suggest that a major portion of residual NCAM expression in the hippocampus is derived from axons projecting to the hippocampus. Furthermore, because NCAM is expressed not only by neurons (Persohn et al, 1989;Prieto et al, 1989) but also by glia (Keilhauer et al, 1985;Noble et al, 1985), and because the ␣CaMKII promoter has not been reported to be active in glia, NCAM expression in the hippocampus may also be attributable to the presence of astrocytes and, less so, oligodendrocytes.…”
mentioning
confidence: 99%
“…N-CAM is also localized to the motor end plate of the myofibril of striated muscle (16). Within the nervous system, N-CAM-180 is found polarized to growth cones (17), to sites of cell-cell contact (18), and to postsynaptic membranes (19). Additionally, N-CAM-180 is polarized to the somatodendritic domain and excluded from axons of mouse hippocampal neurons (20).…”
mentioning
confidence: 99%